Association between usage of household cooking fuel and congenital birth defects-18 months multi-centric cohort study in Nepal - Ashish KC; Sanni Halme; Rejina Gurung; Omkar Basnet; Erik Olsson; Ebba Malmqvist (BMC, 2023)
Abstract Background - An estimated 240,000 newborns die worldwide within 28 days of birth every year due to congenital birth defect. Exposure to poor indoor environment contributes to poor health outcomes. In this research, we aim to evaluate the association between the usage of different type household cooking fuel and congenital birth defects in Nepal, as well as investigate whether air ventilation usage had a modifying effect on the possible association. Methods - This is a secondary analysis of multi-centric prospective cohort study evaluating Quality Improvement Project in 12 public referral hospitals of Nepal from 2017 to 2018. The study sample was 66,713 women with a newborn, whose information was available in hospital records and exit interviews. The association between cooking fuel type usage and congenital birth defects was investigated with adjusted multivariable logistic regression. To investigate the air ventilation usage, a stratified multivariable logistic regression analysis was performed. Results -In the study population (N = 66,713), 60.0% used polluting fuels for cooking and 89.6% did not have proper air ventilation. The prevalence rate of congenital birth defect was higher among the families who used polluting fuels for cooking than those who used cleaner fuels (5.5/1000 vs. 3.5/1000, p < 0.001). Families using polluting fuels had higher odds (aOR 1.49; 95% CI; 1.16, 1.91) of having a child with a congenital birth defect compared to mothers using cleaner fuels adjusted with all available co-variates. Families not using ventilation while cooking had even higher but statistically insignificant odds of having a child with congenital birth defects (aOR 1.34; 95% CI; 0.86, 2.07) adjusted with all other variates. Conclusion - The usage of polluted fuels for cooking has an increased odds of congenital birth defects with no significant association with ventilation. This study adds to the increasing knowledge on the adverse effect of polluting fuels for cooking and the need for action to reduce this exposure.